Cortical Thickness Changes Correlate with Cognition Changes after Cognitive Training: Evidence from a Chinese Community Study - Jiang, Lijuan; Cao, Xinyi; Li, Ting; Tang, Yingying; Li, Wei; Wang, Jijun; Chan, Raymond C.; Li, Chunbo (Frontiers in Aging Neuroscience, 2016)
The aim of this study was to investigate whether changes in cortical thickness correlated with cognitive function changes in healthy older adults after receiving cognitive training interventions. Moreover, it also aimed to examine the differential impacts of a multi-domain and a single-domain cognitive training interventions. Longitudinal magnetic resonance imaging (MRI) scanning was performed on participants 65 to 75 years of age using the Siemens 3.0 T Trio Tim with the MPRAGE sequence. The cortical thickness was determined using FreeSurfer software. Cognitive functioning was evaluated using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). There were significant group × time interaction effects on the left supramarginal, the left frontal pole cortical regions; and a marginal significant group × time interaction effects on visuospatial/constructional and delayed memory scores. In a multi-domain cognitive training group, a number of cortical region changes were significantly positively correlated with changes in attention, delayed memory, and the total score, but significantly negatively correlated with changes in immediate memory and language scores. In the single-domain cognitive training group, some cortical region changes were significantly positively associated with changes in immediate memory, delayed memory, and the total score, while they were significantly negatively associated with changes in visuospatial/constructional, language, and attention scores. Overall, multi-domain cognitive training offered more advantages in visuospatial/constructional, attention, and delayed memory abilities, while single-domain cognitive training benefited immediate memory ability more effectively. These findings suggest that healthy older adults benefit more from the multi-domain cognitive training than single-domain cognitive training. Cognitive training has impacted on cortical thickness changes in healthy elderly. Keywords: Aging, Cognitive function, Cortical thickness, Multi-domain, Single-domain